2013
DOI: 10.7567/jjap.52.07hd02
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal-Type Leaky Surface Acoustic Wave on LiNbO3 with High-Velocity Thin Film

Abstract: The loss reduction of a longitudinal-type leaky surface acoustic wave (LLSAW) by loading with a dielectric thin film with a higher velocity than the substrate is proposed. An aluminum nitride (AlN) thin film was adopted as a high-velocity thin film, and the propagation properties of an LLSAW on an X36°Y-LiNbO3 (LN) substrate were investigated. First, the elastic constants c 11 and c 44 of an amorphous AlN (a-AlN) thin film deposited by RF magnetron sputtering were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
(35 reference statements)
0
16
1
Order By: Relevance
“…It was found from the propagation properties of an LLSAW on an X36°Y-LN substrate that the propagation loss can be reduced from 0.26 dB/ for the sample without a film to 0.15 dB/ by loading with an aluminum nitride (AlN) thin film. 21) A feature of this structure is its similarity to the structure employing a reverse proton exchange (RPE) process to reduce the attenuation of the LLSAW reported by Kakio and Abe, 22) in which the velocity on the surface layer is higher than that on the substrate.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…It was found from the propagation properties of an LLSAW on an X36°Y-LN substrate that the propagation loss can be reduced from 0.26 dB/ for the sample without a film to 0.15 dB/ by loading with an aluminum nitride (AlN) thin film. 21) A feature of this structure is its similarity to the structure employing a reverse proton exchange (RPE) process to reduce the attenuation of the LLSAW reported by Kakio and Abe, 22) in which the velocity on the surface layer is higher than that on the substrate.…”
Section: Introductionmentioning
confidence: 66%
“…3.1 Structure of thin films First, to estimate the effect of the LTS cathode on the surface roughness of AlN thin films, the surface morphology of the deposited thin films with a thickness of approximately 1.0 µm, which were deposited on a SiO 2 glass substrate, was observed by atomic force microscopy (AFM; SII SPA300). Figure 3 shows typical images of the surface morphology of AlN thin films deposited by (a) the LTS-cathode-type system and (b) a planar-type (ANELVA SPF-210A) 21) RF magnetron sputtering system taken over a scanning area of 1 © 1 µm 2 . The rms roughnesses R q over a typical 1 © 1 µm 2 region were determined to be 3.17 and 5.62 nm for the LTS-cathode-type and planar-type RF magnetron sputtering systems, respectively.…”
Section: Evaluation Of Thin Filmsmentioning
confidence: 99%
“…For LLSAW, as well, the attenuation can be controlled by introducing an AlN thin film or forming an RPE layer. [88][89][90] However, K 2 was reduced owing to the low piezoelectricity of the RPE layer and AlN thin film.…”
Section: Control Of Lsaw Properties Using Layered Structuresmentioning
confidence: 99%
“…To increase the frequency of SAW resonators, the utilization of longitudinal leaky SAWs (LLSAWs) with a phase velocity of 1.5-2 times that of conventional LSAWs has been studied. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, our research group has reported that, by bonding a piezoelectric LiTaO 3 (LT) or LiNbO 3 (LN) thin plate, having a thickness of less than one wavelength (1 λ), to a high-phase velocity support substrate such as quartz (Qz), LLSAWs with a large Q and K 2 of 2-3 times of that of a single LT or LN can be produced owing to a strong concentration of particle displacement in the thin plate. 9,[12][13][14][15] Several research groups, including ours, have reported that bonded structures comprising an LT or LN thin plate and Qz support substrate exhibit high-performance properties with wider FBW, higher Q factor, and better temperature coefficient of frequency than those in the single substrate for LSAWs.…”
Section: Introductionmentioning
confidence: 99%